Expressões de uma “vingança adiada”: o kit gay e a mamadeira de piroca como movimentos performativos na linguagem - Menezes, Carlos André Araújo (2024)
The 2018 presidential election was deeply marked by narrative wars around social markers such as gender, race and class. Brazil went through its political dispute sharing fake news (Dunker, 2019; Fuks, 2019; Tezza, 2019; Mello, 2020; Santaella, 2020). The vast majority of the campaign's fake news mentioned an alleged "gay kit" and a "dick botle", thus provoking a moral and gender panic in a large part of the Brazilian population (Miskolci, 2009), which drove many brazilians to join Jair Messias Bolsonaro's conservative political project, who, at the time, in fulfillment of an intercontinental agenda, promised to restore old moral values of the "traditional family", as well as blocking recent advances in public policies that guaranteed historical rights to the LGBTQIPAN+ population (Pesavento, 1995; Petó, 2015; Kuhar; Paternotte, 2017; Leite, 2019). The main hypothesis of this research is that the affect of resentment (Kehl, 2020; Nietzsche, 2020a, 2020b; Giacoia, 2021) mobilized a large part of the Brazilian population to adhere to the aforementioned conservative political project. The main objective of this dissertation was to investigate the ways in which resentment was mobilized in some fake news stories that mentioned the terms "gay kit" and "dick bottle". the specific objectives were: 1. I Identified the persuasive strategies present in the video “A mamadeira que mudou o Brasil”, situating moral values and concepts and resentment between social groups; 2. I compared the discourses focused on educational practices present in some news reports and mentioned the term gay kit, situating the intertexts that made up its network of meanings, finally: 3. I investigated, in the music video “Kit gay”, by Detonautas, what forms of resistance were mobilized after the 2018 Brazilian election campaign. In order to achieve its objectives, the corpus of this research was problematized with: Austin (1990); Butler (2015, 2021); Foucault (2017, 2014a, 2014b, 2005, 1994) and Derrida (1991) who respectively thought of language as an anti-idealist and deconstructed principle, as a saying-doing action, also as a performance. These theoretical frameworks have helped me to think about discursive practices and the performative actions of/in language, marking it out as a living social instance, situated in sociocommunicative practices. Methodologically, the path chosen to produce the data was anchored in more recent Applied Linguistics (Pennycoock, 2006; Moita Lopes, 2021, 2023) and the genealogical method (Nietzsche and Foucault). The use of LA allowed for various intersections between language studies and other fields of study, and sought, from these intersections, to think about issues that had an impact on social life. The results pointed to a deep agency of the Brazilian population by conservative religious groups and strong resentment, which culminated in the victory of Jair Messias Bolsonaro in 2018 and whose effects have put and still put at risk Brazil's recent democracy.